2020
DOI: 10.1155/2020/2489407
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Like Receptor 3 Agonist Polyriboinosinic Polyribocytidylic Acid Increases the Numbers of NK Cells with Distinct Phenotype in the Liver of B6 Mice

Abstract: One of the activating factors of the cells of the innate immune system is the agonists of toll-like receptors (TLRs). Our earlier publications detailed how poly(I:C), a TLR3 agonist, elevates the NK cell population and the associated antigen-specific CD8+ T cell responses. This study involved a single treatment of the B6 mice with poly(I:C) intraperitoneally. To perform a detailed phenotypic analysis, mononuclear cells were prepared from each of the liver, peripheral blood, and spleen. These cells were then ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, our group established poly(I:C) as a potent adjuvant in vaccination regimens (Salem, 2005;Salem, 2006;Salem, 2009;Salem, 2007;Salem et al, 2020). We then conducted the same experiment except this time administering vaccination with or without poly(I:C) on day 7 after adoptive cell transfer and analyzed the cell numbers in the peripheral blood on day 12.…”
Section: Cpg-induced Proliferation Of B Cells Associates With Their A...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our group established poly(I:C) as a potent adjuvant in vaccination regimens (Salem, 2005;Salem, 2006;Salem, 2009;Salem, 2007;Salem et al, 2020). We then conducted the same experiment except this time administering vaccination with or without poly(I:C) on day 7 after adoptive cell transfer and analyzed the cell numbers in the peripheral blood on day 12.…”
Section: Cpg-induced Proliferation Of B Cells Associates With Their A...mentioning
confidence: 99%
“…In this context, we have reported that the TLR3L poly(I:C) is a potent adjuvant for CD8 + T cell responses, through increasing T cell number, function, cytokine production, and anti-tumor response 7,20,21 . These adjuvant effects were associated with increases in the by increasing the numbers of dendritic cells in mice 20,22 and in pancreatic cancer patients as well as increases in the numbers of NK cells in mice 23 . In addition, in vivo administration of poly(I:C) at the peak of dendritic cell (DC) expansion aftercyclophosphamide treatment induces in ammatory cytokine production and increases in the number of activated DCs in lymph nodes 22 .…”
Section: Introductionmentioning
confidence: 99%